A Mercury Ion Electrochemical Sensor Based on Porous Anodized Alumina Membrane Nanochannels Modified with DNA. Issue 11 (1st January 2018) - Mo, Rijian; Yuan, Qiong; Yan, Xiemin; Su, Tiantian; Feng, Yanting; Lv, Lulu; Zhou, Chunxia; Hong, Pengzhi; Sun, Shengli; Li, Chengyong
Abstract : A novel mercury ion (Hg 2+ ) electrochemical sensor was established via chemical modification of porous anodic alumina (PAA) membrane nanochannels with DNA. PAA membrane was prepared by a two-step anodization. Amino groups were introduced to nanochannels by silanization. Special sequence DNA (along with amino group) was modified on PAA membrane nanochannels by the condensation reaction of amino and aldehyde groups. Electrochemical detector was built via sputtered Au nanoparticles on the surface of PAA nanochannels, which could be used as working electrode. The reduction potential of 0 V was applied, where the flux of Fe(CN)6 3− was determined by diffusion. The current response has a positive correlation with the concentration of Fe(CN)6 3− . After DNA immobilized, the negative charge and the steric hindrance of the nanochannels is increased, resulting in the decreasing of the flux of Fe(CN)6 3− . The detection current is reduced compared with pure PAA membrane nanochannels. When Hg 2+ is present, a stable thymine-Hg 2+ -thymine structure is formed due to the specific reaction between thymine in DNA and Hg 2+ . In this case, the charge density and steric hindrance of the nanochannels are decreased, thereby increasing the flux of Fe(CN)6 3− and restoring current. The results show that the detection limit is about 0.08 pM with a good linear response (from 1 pM to 100 nM). Meanwhile, the sensor has a good selectivity. The current responses of other metal ions (Mn 2+, Mg 2+, Ba 2+, Co 2+ and Cd 2+ ) are not obvious compared with Hg 2+ . Therefore, this new sensor could be applied for detecting Hg 2+ in the environment.